Volume imaging to interrogate cancer cell-tumor microenvironment interactions in space and time - Almagro, Jorge; Messal, Hendrik A. (Frontiers in Immunology, 2023)
Volume imaging visualizes the three-dimensional (3D) complexity of tumors to unravel the dynamic crosstalk between cancer cells and the heterogeneous landscape of the tumor microenvironment (TME). Tissue clearing and intravital microscopy (IVM) constitute rapidly progressing technologies to study the architectural context of such interactions. Tissue clearing enables high resolution imaging of large samples, allowing the characterization of entire tumors and even organs and organisms afflicted with cancer. With IVM, the dynamic engagement between cancer cells and the TME can be visualized in 3D over time (4D imaging). Together, tissue clearing and IVM have been critical to examine cancer-TME interactions, and have drastically advanced our knowledge in fundamental cancer research and clinical oncology. This review provides an overview of the current technical repertoire of fluorescence volume imaging technologies to study cancer and the TME and discusses how their recent applications have been applied to advance our fundamental understanding of tumor architecture, stromal and immune infiltration, vascularization and innervation, and to explore avenues for optimized chemotherapy delivery and efficacy of immunotherapy.